Cleavage of the N2 triple bond by the Ti dimer: a route to molecular materials for dinitrogen activation? - Himmel, Hans-Jörg; Hübner, Olaf; Klopper, Wim; Manceron, Laurent (Angewandte Chemie. International edition, 2006)
The Ti dimer is fairly weakly bound, but highly reactive, and completely cleaves the strong N2 triple bond in just one step without activation energy (see scheme; Ti red, N blue).
Gesehen am 14.03.2018